2008
DOI: 10.1016/j.childyouth.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

How to open and sustain a drop-in center for homeless youth

Abstract: Drop-in centers have the potential to facilitate engagement of homeless youth into treatment and back into the mainstream. However, little guidance was found in the literature regarding how to open and sustain a drop-in center for homeless youth. This paper offers such guidance, including information that may be useful for developing a change philosophy that guides the center structure, and for identifying a building and location conducive to facilitate activities and access for the youth. Guidance for structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Rigorous reporting by the New York Times [31] portrays homeless young people as vulnerable, resilient, self-reliant, suspicious of adults and institutions, and, once ensconced in homeless culture, very difficult to reach and help, even by dedicated experts. This journalistic picture is largely consistent with research which characterizes homeless young people by a present-focus on basic needs rather than longer-term goals, by a desire for self-reliance but vulnerable to older people who seek economic advantage (e.g., pimps or drug dealers), and by a general suspicion of adults and institutions but in need of help and services for personal development [4,20,27,33].…”
Section: Introductionmentioning
confidence: 57%
“…Rigorous reporting by the New York Times [31] portrays homeless young people as vulnerable, resilient, self-reliant, suspicious of adults and institutions, and, once ensconced in homeless culture, very difficult to reach and help, even by dedicated experts. This journalistic picture is largely consistent with research which characterizes homeless young people by a present-focus on basic needs rather than longer-term goals, by a desire for self-reliance but vulnerable to older people who seek economic advantage (e.g., pimps or drug dealers), and by a general suspicion of adults and institutions but in need of help and services for personal development [4,20,27,33].…”
Section: Introductionmentioning
confidence: 57%
“…The development of this relationship is hypothesized to be the key mechanism for guiding young people out of homelessness (Slesnick et al, 2008). As has been discussed, a place for engaging this progression is constructed, in part, out of the information resources that are presented.…”
Section: Resultsmentioning
confidence: 99%
“…Yet young people must develop knowledge for navigating this system if they are to meet their basic needs and take steps that lead out of homelessness (Ammerman et al, 2004). On the other hand, research has also shown that homeless people are overwhelmed by this system and experience great difficulty obtaining needed information and services (Hersberger, 2002;Slesnick et al, 2008). A key goal of service providers, therefore, is helping to guide young people through this system.…”
Section: What Is Homelessness?mentioning
confidence: 99%
See 2 more Smart Citations